SEMIOTIC AND MULTIMODAL REPRESENTATION OF EXISTENTIAL CONFLICT IN FICTIONAL DISCOURSE - Olha V. Chernenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
The article represents an attempt to build and apply a linguosemiotic model of existential conflict research in modern English fictional discourse. The modern tendency of philological and socio-humanistic studies to involve the tools of semiotics, discourse theory, and multimodality in the process of complex analysis of a literary work as an artistic model of reality is highlighted. The research is based on practical blocks of illustrative material, selected discursive fragments from a literary work, which contain an existential conflict. Basically, the key point here is the analysis of intra- and interpersonal conflict based on the theoretical achievements of semiotics and linguosemiotics (Ch. Pierce, Yu. Lotman, U. Eco, G. Pocheptsov) and the theory of discourse and multimodality (G. Kress, K. O’Halloran, C . Forceville, M. Halliday). It makes it possible to provide a detailed research of existential conflict in fictional discourse with the identification of latent, ambivalent meanings and the relevant reconstruction and interpretation of the conflict by the reader. The paper aims at projecting the modern tendency towards the synergy of various aspects of conflict studies across the humanities. Therefore, the goal of the paper is to outline the advantages of an integral approach to the study of conflict in modern linguistic conflictology and to build a linguosemiotic model for the analysis and interpretation of existential conflict in fictional discourse. Thus, the paper`s core objectives involve: 1) to study the achievements of the semiotic and multimodal approach in its application to synthetic level communicative systems containing conflict; 2) to reveal the place, role and potential of the existential conflict in fictional discourse using the above-mentioned methods; 3) to present a linguosemiotic model for the study of existential conflict in modern English fictional discourse. The theoretical and methodological base of the research involves general-scientific methods of analysis, synthesis, deduction as well as the method of linguosemiotic and multimodal analysis to determine the components of semiosis of existential intrapersonal conflict in fictional discourse. The results of the research consist in the creation of an integral semiotic model of the analysis of existential conflict in modern English-language fictional discourse, which assumes the presence of a static and dynamic component in its structure, revealed, in particular, in the process of semiotic reading of the work in three successive stages of mimesis, semiosis, and synthesis. The process of conflict interpretation presupposes a comprehensive approach to semiotic reading activity developed in consecutive steps. The linguosemiotic means of representing the existential conflict at different levels of the literary work, which have a multimodal nature, have been revealed. The temporal, psychological, and sign-symbolic characteristics of the existential conflict, which make up the semiotic space or semiosphere of the literary work, are analyzed and classified. As a result of the identification and unification of the factors that determine the way of development of existential conflict in fictional discourse, the linguosemiotic model of the analysis of this type of intrapersonal conflict was reconstructed. The model covers the study of the semiotic components of the sign-symbolic, psychological and temporal space and the surface and deep levels of the semiotic reading of the literary work, at which the cognitive, behavioral and emotional aspects of the conflict are decoded and reconstructed.